Design of a light tracking system using machine vision technique - Kareem, Samir A. Abdul; Akmeliawati, Rini; Muhida, Riza (2011)
A two degree of freedom (DOF) light tracking system is presented in this paper. It uses a web camera as a vision sensor, PC sound cards as output signal controllers, and two DC motors as a pan-tilt driver mechanism. The sound card is expected to produce a higher output signal in a PWM form to drive the motors. The motors will react accordingly when they receive the signals to ensure that the camera always focuses on the centroid of the light source. The system used image processing technique to detect and determine the location of the light source and was programmed to send PWM through the sound card to drive the motors to correct the error produced from the light movement. In MATLAB programming environment, a closed-loop control is implemented to provide interaction between camera and sound cards as devices to control the motors to track the light source. The system has been designed and tested with various locations of light source. The data which were obtained by experiments indicate the ability of the proposed controller.